Effect of CaO/Fe2O3 ratio on slag viscosity behavior under entrained flow gasification conditions. (15th December 2019) - Ge, Zefeng; Kong, Lingxue; Bai, Jin; Zhao, Huiling; Cao, Xi; Li, Huaizhu; Bai, Zongqing; Meyer, Bernd; Guhl, Stefan; Li, Ping; Li, Wen
Highlights: As CaO/Fe2 O3 ratio decreased, slag viscosity at same temperatures decreased. A linear relationship between slag viscosity and CaO/Fe2 O3 ratio was established. The decrease in CaO/Fe2 O3 ratio was favor of the growth of crystalline phases. Crystal growth changed from surface crystallization to bulk crystallization. The results provided a guide for using CaO-Fe2 O3 binary composite flux in entrained flow gasification. Abstract: The key factor for smooth slag tapping of entrained flow gasifiers was slag viscosity behavior. Shanxi coals can't meet the requirement for discharging slag due to its high SiO2  + Al2 O3 contents. The single fluxing agent (CaO or Fe2 O3 ) was also inoperative for Shanxi coals. Hence, the development of binary composite flux was urgent and necessary. The effect of CaO-Fe2 O3 binary composite flux on slag viscosity temperature behavior was investigated in this work. As the CaO/Fe2 O3 ratio decreased, the slag viscosity at same temperatures decreased. Furthermore, a linear relationship between the slag viscosity and CaO/Fe2 O3 ratio was established at high temperatures. Characterization of slag structure showed that the polymerization degree decreased with the decreasing CaO/Fe2 O3 ratio. The calculated BO/(BO + NBO) (fraction of bridging oxygen) also presented an excellent linear relationship with CaO/Fe2 O3 ratio. This indicated that CaO/Fe2 O3 ratio affected the slag structure, leading to the variation of slag viscosity. During the cooling step, the crystallization activation energy E c was used to describe the effect of CaO/Fe2 O3 ratio on slag crystallization behavior quantitatively. Besides, the growth pattern of crystal phases transformed from the surface crystallization to the bulk crystallization with the decreasing CaO/Fe2 O3 ratio, and the bulk crystallization was more easily to promote the crystallization behavior. In brief, slag viscosity and crystallization behavior could be modified via adjusting CaO/Fe2 O3 ratio. These results can provide a guide for using CaO-Fe2 O3 binary composite flux to improve the slag viscosity behavior in entrained flow gasification.